2011
DOI: 10.1111/j.1748-1716.2010.02219.x
|View full text |Cite
|
Sign up to set email alerts
|

Plasticity in vagal afferent neurones during feeding and fasting: mechanisms and significance*

Abstract: The ingestion of food activates mechanisms leading to inhibition of food intake and gastric emptying mediated by the release of regulatory peptides, for example cholecystokinin (CCK), and lipid amides, e.g. oleylethanolamide from the gut. In addition, there are both peptides (e.g. ghrelin) and lipid amides (e.g. anandamide) that appear to signal the absence of food in the gut and that are associated with the stimulation of food intake. Vagal afferent neurones are a common target for both types of signal. Remar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
57
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
3
3
1

Relationship

0
7

Authors

Journals

citations
Cited by 56 publications
(58 citation statements)
references
References 76 publications
0
57
1
Order By: Relevance
“…In order to further clarify the mechanism behind the observed beneficial effects in the current study, we assessed aspects of indirect calorimetry following 18 days' treatment with (pGlu-Gln)-CCK-8, [D-Leu-4]-OB3 or a combination of both peptides. Although extensive studies have been conducted on the additive effects of leptin and CCK on energy intake [4], there is much less information on their possible combined effects on locomotor activity and energy expenditure. Explorative episodes (Z-beam breaks) were elevated during the dark phase but reduced during the light phase in all mice treated with (pGlu-Gln)-CCK-8, with no overall net effect.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In order to further clarify the mechanism behind the observed beneficial effects in the current study, we assessed aspects of indirect calorimetry following 18 days' treatment with (pGlu-Gln)-CCK-8, [D-Leu-4]-OB3 or a combination of both peptides. Although extensive studies have been conducted on the additive effects of leptin and CCK on energy intake [4], there is much less information on their possible combined effects on locomotor activity and energy expenditure. Explorative episodes (Z-beam breaks) were elevated during the dark phase but reduced during the light phase in all mice treated with (pGlu-Gln)-CCK-8, with no overall net effect.…”
Section: Discussionmentioning
confidence: 99%
“…It is widely acknowledged that the major physiological role of CCK is in the short-term stimulation of satiety [4]. Specifically, the actions of CCK on food intake are mediated peripherally by CCK 1 receptors on vagal afferent neurons [4]. Indeed, peripherally released CCK cannot penetrate the blood-brain barrier [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The first site of integration of these signals occurs at the level of vagal afferent neurons (VAN), which project to and stimulate second-order neurons in the dorsal vagal complex of the hindbrain (27). VAN express receptors for many of the anorexigenic and orexigenic hormones released from the gut wall and mediate changes in gastrointestinal function and food intake in response to luminal nutrients (18).…”
mentioning
confidence: 99%
“…In the present study, it was demonstrated that the ablation of ARP neurons markedly induced Egr1 expression in the majority of known targets of POMC and ARP neurons, indicating that the loss of ARP neurons leads to disinhibition of postsynaptic neurons, which eventually results in anorexia. Egr1 has been observed to stimulate CART expression in certain types of neurons (17,23). CART peptides are widely distributed in the CNS and are known to suppress food intake (24,25) and stimulate Fos expression in a number of brain areas when administered centrally (26,27).…”
Section: Disscussionmentioning
confidence: 99%